2019
DOI: 10.3390/cancers11030351
|View full text |Cite
|
Sign up to set email alerts
|

Development of DNA Aptamers to Native EpCAM for Isolation of Lung Circulating Tumor Cells from Human Blood

Abstract: We selected DNA aptamers to the epithelial cell adhesion molecule (EpCAM) expressed on primary lung cancer cells isolated from the tumors of patients with non-small cell lung cancer using competitive displacement of aptamers from EpCAM by a corresponding antibody. The resulting aptamers clones showed good nanomolar affinity to EpCAM-positive lung cancer cells. Confocal microscopy imaging and spectral profiling of lung cancer tissues confirmed the same protein target for the aptamers and anti-EpCAM antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The great supremacy in development of technology for new aptamers and second generation analogs, such as X‐Aptamers (XAs), SOMAmers, locked nucleic acids (LNAs), suggests aptamers are promising as a theranostic tool in clinical setting in near future. Recently, DNA aptamers were selected against EpCAM expressed on primary lung cancer cells, and then successfully applied to isolation and detection of circulating tumor cells in blood samples of lung cancer patients . Aptamers have also been used to design electrochemical aptamer‐based biosensors for the detection of specific cancer cell markers in blood samples …”
Section: Aptamer Emerges As a Prominent Targeting Ligand For Nanodelimentioning
confidence: 99%
“…The great supremacy in development of technology for new aptamers and second generation analogs, such as X‐Aptamers (XAs), SOMAmers, locked nucleic acids (LNAs), suggests aptamers are promising as a theranostic tool in clinical setting in near future. Recently, DNA aptamers were selected against EpCAM expressed on primary lung cancer cells, and then successfully applied to isolation and detection of circulating tumor cells in blood samples of lung cancer patients . Aptamers have also been used to design electrochemical aptamer‐based biosensors for the detection of specific cancer cell markers in blood samples …”
Section: Aptamer Emerges As a Prominent Targeting Ligand For Nanodelimentioning
confidence: 99%
“…Aptamers are a kind of small oligonucleotides (e.g., DNA, RNA, or peptides) with the ease of binding to molecular and cellular components . Furthermore, they are easily synthesized and separated with high sensitivity and specificity through a systematic evolution of ligands by exponential enrichment (SELEX) process which is the key feature of aptamers used for CTCs' isolation . Hence, the aptamer‐functionalized nanostructures were introduced to increase topographic interactions between targeted CTCs and surface coated with specific antibodies, giving rise to recovered CTCs' isolation with satisfactory capture efficiency …”
Section: D Microfluidic Platforms For Ctcs' Detection and Isolationmentioning
confidence: 99%
“…In addition to differential approaches, whole-living cell-based protocols have been applied by the same group for the selection of aptamers against NSCLC-related known targets [ 20 ]. The authors addressed the selection of DNA aptamers against the epithelial cell adhesion molecule (EpCAM), a marker expressed at high levels by many carcinomas as well as by circulating tumor cells [ 21 , 22 ].…”
Section: Selex Technologies To Generate Nsclc Targeting Aptamersmentioning
confidence: 99%
“…The possibility to use aptamers for the detection of CTCs was also described by Zamay et al [ 19 , 20 ]. They found that fluorescently labeled aptamers selected against lung adenocarcinoma cells from postoperative tissues, when applied to patients’ peripheral blood samples, were able to detect CTCs, with a specificity of 76% and a sensitivity of 86% [ 19 ].…”
Section: Nucleic Acid Aptamers For Nsclc Detectionmentioning
confidence: 99%
See 1 more Smart Citation